2000
DOI: 10.1093/hsw/25.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Social Work and Family Medicine: A Partnership in Community Service

Abstract: Traditionally, family physicians have been called on to handle the emotional problems of their patients. Their ability to address these concerns has been inconsistent. In hospital settings, where interdisciplinary teams are common, nonmedical professionals have been able to provide counseling services to patients. But this is a problem in private medical practices. This article presents a model for collaboration between family medical and clinical social work practice and describes a holistic approach for prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Specific attributes noted include the holistic, ecological views of, and approaches to, health (Brochstein, Adams, Tristan, & Cheney, 1979;Goldberg, Neill, Speak, & Faulkner, 1968;Netting & Williams, 1996;Rock & Cooper, 2000), a commitment to indigenous models of practice (Brochstein et al, 1979) and extensive community networks (Backett, Maybin, & Dudgeon, 1957;Dongray, 1958;Goldberg et al, 1968;Lesser, 2000).…”
Section: Original Articlementioning
confidence: 99%
See 2 more Smart Citations
“…Specific attributes noted include the holistic, ecological views of, and approaches to, health (Brochstein, Adams, Tristan, & Cheney, 1979;Goldberg, Neill, Speak, & Faulkner, 1968;Netting & Williams, 1996;Rock & Cooper, 2000), a commitment to indigenous models of practice (Brochstein et al, 1979) and extensive community networks (Backett, Maybin, & Dudgeon, 1957;Dongray, 1958;Goldberg et al, 1968;Lesser, 2000).…”
Section: Original Articlementioning
confidence: 99%
“…In the international arena, many factors have led to the integration of social workers within PHCPs such as enhanced communication and cooperation between social workers and medical staff (Lesser, 2000) and the strategic provision of timely, early, preventive social care without the need to refer to specialised services (Dongray, 1958;Goldberg et al, 1968;Laden, Oehlers, Waddell, & Miller, 1983;Wilson & Setturlund, 1987). Models of social work in PHC have been shown to ease access for populations such as ethnic minorities and people from a lower socio-economic background, who otherwise may experience barriers to health services (Lesser, 2000;Lymbery & Millward, 2002;Rizzo & Mizrahi, 2008).…”
Section: Original Article Qualitative Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps their absence in this setting reinforces the perception by providers and patients alike that social workers are ill equipped to address complex and holistic problems such as somatization (Lesser, 2000). Social workers are often relegated to the tasks of discharge planning rather than looked upon as a formidable discipline with mental health expertise and equal credibility with the medical provider (Cowles, & Lefcowitz, 1995).…”
Section: Importance For Social Workmentioning
confidence: 99%
“…[8][9][10] Positive outcomes have been reported as a result of social work involvement in PHC practices, such as enhanced communication 11 and easier access for ethnic minorities and people of low socioeconomic status. [11][12][13] Further, people who experienced psychosocial issues and did not access an external social service agency indicated their interest in getting or accepting an offer of integrated social work support. 14,15 One study identified terrorism and other catastrophes (such as natural disasters) as appropriate psychosocial issues to be addressed by social workers based within PHC practices.…”
Section: Introductionmentioning
confidence: 99%